Prevalence of refractive errors in Villa Maria, Córdoba, Argentina - SánchezVictoria M.; IribarrenRafael; LatinoSantiago G.; TorresVictor E.; GramajoAna L.; ArtalMaría N.; YadarolaMaría B.; GarayPatricia R.; LunaJosé D.; JuarezClaudio P. (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
Background: Refractive errors are among the most frequent reasons for demand of eye-care services. Publications on refractive errors prevalence in our country are few. This study has the purpose to assess the prevalence of refractive errors in an adult population of Villa Maria, Córdoba, Argentina. Methods: The Villa Maria Eye Study is a population-based cross-sectional study conducted in the city of Villa Maria, Córdoba, Argentina from May 2008 to November 2009. Subject’s aged 40+ received a demographic interview and complete ophthalmological exam. Visual acuity was obtained with an ETDRS chart. Cycloplegic auto refraction was performed. The spherical equivalent was highly correlated between right and left eyes, so only data of right eyes are presented. Myopia and hyperopia were defined with a ±0.50 diopters (D) criterion and astigmatism >1 D. Results: This study included 646 subjects, aged 40 to 90 (mean age: 59.6±10.3 years old). Four hundred and sixty two (71.5%) were females. The mean spherical equivalent was +0.714±2.41 D (range, −22.00 to +8.25 D) and the power of the cylinder was, on average, −0.869±0.91 D (range, 0 to −6.50 D). In this sample, 61.6% subjects were hyperopic, and 13.5% were myopic. Myopia prevalence was lower in men (9.8% versus 14.9%) but this difference among genders was not statistically significant. There were 141 subjects (21.8%) with anisometropia greater than 1 D, and 168 subjects (26.0%) with astigmatism greater than 1 D. Conclusions: The present study shows the prevalence of cycloplegic refractive errors in an adult population of Argentina. The prevalence of hyperopia was high, while myopia prevalence was very low.